Care Needs of Elderly Migrants in Austria - Perchinig, Bernhard; Schaur, Katharina (Lidé města, 2016)
In Austria, migrants who arrived in the 1960s and 70s (“guestworkers”) were often supported very little in terms of language classes, education and other integration measures, as they were expected (and often themselves expected) to return to their country of origin eventually. In fact, most “guest workers” and their families became permanent residents. Now, the ageing of this generation of unexpected residents poses myriad challenges to the Austrian health care system. Although these challenges were foreseeable, care providers and state institutions have been reluctant to respond or are only lately beginning to respond to migrants’ needs, in particular the need of language translation services and culturally sensitive approaches. This paper provides an empirical perspective on these challenges from ex- Yugoslav, Turkish and Philippine elderly migrants’ point of view. For them, three topics interlink: On the individual level, they often face difficult access to a health care system that is not reflective of migrants’ needs; at the level of the older generation – their own parents and in-laws –, responding to care obligations for relatives still residing in the country of origin conflicts with the regulations of migration regimes; and at the level of the younger generation – their children –, there are many open questions and tensions around care expectations which the younger generation may be unwilling or unable to fulfil. The paper is based on a research project funded by the Austrian Ministry of Foreign Affairs and Integration, which aimed to analyse care needs and expectations of elderly migrants from the origin countries of ex-Yugoslavia, Turkey, and the Philippines. Methodologically, the study is based on analysis of literature and a quantitative estimate of migrants in elderly care for the next 10 years. Furthermore, 30 interviews with Austrian experts in federal administration, care providers, professional networks, relevant NGOs, as well as academic experts were conducted. Finally, the study aimed to explore migrants’ perspectives through 8 focus groups with overall 74 participants organized in the cities of Linz and Vienna.